The Impact of the COVID-19 Pandemic on Sexual Health in Cis Women Living in Germany. Issue 6 (6th March 2022) - Batz, Falk; Lermer, Eva; Hatzler, Laura; Vilsmaier, Theresa; Schröder, Lennard; Chelariu-Raicu, Anca; Behr, Joachim; Mahner, Sven; Buspavanich, Pichit; Thaler, Christian J.
ABSTRACT: Background: Preliminary research shows a substantial impact of the COVID-19 pandemic on women's sexual health, whereby empirical work on sexual well-being of minoritized sexual identities is still rare. Aim: The objective of this study was to explore sexual health in heterosexual, lesbian and bisexual cis women during the first wave of COVID-19 pandemic in Germany. Methods: An anonymous nationwide online survey was conducted among cis women during the first nationwide lockdown in Germany from April 20th to July 20th, 2020. The questionnaire was distributed via e-mail, online chats and social-media platforms. Outcomes: Demographic variables and self-report measures from the Sexual Behavior Questionnaire (SBQ-G) "before the pandemic" and "since the pandemic" were collected. Results: A total of 1, 368 cis women participants were included: heterosexual women (n = 844), lesbian women (n = 293), bisexual women (n = 231). Results indicate overall decrease in frequency of sexual contacts and masturbation during the COVID-19 pandemic. Regarding differences before and during the pandemic lesbian women showed significant changes in sexual arousal whereas heterosexual women showed significant changes in all dimensions except capability to enjoy sexual intercourse. The data of bisexual women showed significant changes in almost all dimensions except for frequency of sexual intercourse and sexual arousal. Results of the multiple regression analysis revealed that being younger than 36 years-old, and being in a relationship as well as being heterosexual (compared with being lesbian) is positively associated with general satisfaction with sexual life during the pandemic. Clinical Implications: The findings suggest that during a pandemic sexual and mental health care for (cis) women should be provided and address the specific needs of sexual minority groups. Strengths & Limitations: This is the first study to describe sexual behavior in heterosexual, lesbian and bisexual women during the COVID-19 pandemic in Germany. Limitations, however, include the fact that the data described were obtained at only one time point so there is a possibility of recall bias, and that the results cannot be generalized because of the underrepresentation of women over age 46. Conclusion: This study examined the impact of the COVID-19 pandemic and resulting social constraints on the sexual health of particular groups of lesbian and bisexual women, which may improve preparedness for future public health and policy crises.